Exploring emotional states and surprising consumption as drivers of engagement at music festivals - Sarmento, Eduardo Moraes (2021)
The aim of the current study is to explore the relationship between visitors' emotional states and surprise consumption with visitors' engagement at festivals in Portugal. A sample of usable questionnaires allowed us to understand that surprising consumption and arousal are very important drivers to engage visitors to music festivals. The article also provides managerial implications, limitations and further research